2015
DOI: 10.1186/s40537-015-0015-2
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment analysis using product review data

Abstract: Sentiment analysis or opinion mining is one of the major tasks of NLP (Natural Language Processing). Sentiment analysis has gain much attention in recent years. In this paper, we aim to tackle the problem of sentiment polarity categorization, which is one of the fundamental problems of sentiment analysis. A general process for sentiment polarity categorization is proposed with detailed process descriptions. Data used in this study are online product reviews collected from Amazon.com. Experiments for both sente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
223
0
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 617 publications
(241 citation statements)
references
References 18 publications
2
223
0
16
Order By: Relevance
“…The parameters provided in Table 3 below compares the area covered under ROC curve between the works done by Fang and Zhang (2015) with the results obtained from the current work presented in Figure 8. They used Naïve Bayesian Classifier on the product features data for the task of sentiment analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The parameters provided in Table 3 below compares the area covered under ROC curve between the works done by Fang and Zhang (2015) with the results obtained from the current work presented in Figure 8. They used Naïve Bayesian Classifier on the product features data for the task of sentiment analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Authors Xing Fang, Justin Zhan [2] did experiments for two types of classification. First, sentence-level classification and review-level classification and also achieved good results.…”
Section: Supervised Machine Learning Approachmentioning
confidence: 99%
“…Saif H., et.al. [3] In this paper, they provided an overview of eight publicly available and manually annotated evaluation datasets for Twitter sentiment analysis. They found that unlike the tweet level, very few annotation efforts were spent towards providing datasets for evaluating sentiment classifiers at the entity level.…”
Section: Organisation Of Papermentioning
confidence: 99%
“…Precision is calculated using equation (3). From the bar graph {1} it is clear that Multinomial Naïve Bayes algorithm gives better precision than Naïve Bayes algorithm.…”
Section: Iosr Journal Of Computer Engineering (Iosr-jce) E-issn: 2278mentioning
confidence: 99%